Dampak Kerjasama Pendidikan Singapura – Laos Melalui Singapore Cooperation Programme (SCP) Terhadap Human Capital Di Laos - Husnain, Fikri Arfiansyah (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
Singapore is a country with the best education system in Southeast Asia. With supportive education policies and excellent education facilities, Singapore can build a good education system to become one of the countries with the best education system in the world. As one of the ASEAN member countries, Singapore is encouraged to help other ASEAN member countries as stated in the ASEAN policy on inclusive education cooperation between member countries. Laos as one of the ASEAN member countries with an inadequate education system is one of the member countries that cooperates with Singapore in improving its education system. The low quality of a country's education system can affect the quality of human capital in that country and vice versa, the high quality of a country's education system can improve the quality of its country's human capital. Through the Singapore Cooperation Programme (SCP) Singapore and Laos conduct educational cooperation that will play an important role in human capital in Laos. This research aims to analyze the impact of Singapore-Laos educational cooperation through the Singapore Cooperation Programme (SCP) on human capital in Laos. This research uses descriptive qualitative method as an approach in exploring certain social problems by describing reality correctly. As for data collection using literature study techniques. The sources related to data data in research involve data collection and analysis of information from previous works such as, scientific journals, official government websites, books, e-books, media and scientific articles relevant to the object of research.